2000
DOI: 10.1017/s135583820099229x
|View full text |Cite
|
Sign up to set email alerts
|

A new twist in trypanosome RNA metabolism: cis-splicing of pre-mRNA

Abstract: It has been known for almost a decade and a half that in trypanosomes all

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
121
0
8

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(130 citation statements)
references
References 23 publications
1
121
0
8
Order By: Relevance
“…In trypanosomes, all the RNAs are processed by a mechanism different from that in mammals (cis-splicing) called trans-splicing, a process that involves the union of the exons in two independent transcripts. However, in recent studies it was observed that cis-splicing can also occur in the gene PAP (poly-A polymerase) of Trypanosoma brucei and T. cruzi, suggesting that both trans and cis-splicing, occur in these parasites, with a predominance of trans-splicing (Mair et al 2000).The SL RNA or miniexon is a primary transcript synthesized independently of pre-mRNA and trans-spliced in all nuclear mRNA. The majority of mRNAs is synthesized as polycistronic precursors (Agabian 1990).…”
mentioning
confidence: 99%
“…In trypanosomes, all the RNAs are processed by a mechanism different from that in mammals (cis-splicing) called trans-splicing, a process that involves the union of the exons in two independent transcripts. However, in recent studies it was observed that cis-splicing can also occur in the gene PAP (poly-A polymerase) of Trypanosoma brucei and T. cruzi, suggesting that both trans and cis-splicing, occur in these parasites, with a predominance of trans-splicing (Mair et al 2000).The SL RNA or miniexon is a primary transcript synthesized independently of pre-mRNA and trans-spliced in all nuclear mRNA. The majority of mRNAs is synthesized as polycistronic precursors (Agabian 1990).…”
mentioning
confidence: 99%
“…Since no removal of introns is necessary in the mRNA processing of T. cruzi, alternative cis-splicing should be uncommon. Until now, few experimental works have demonstrated alterations in protein composition due to alternative cis-splicing (Mair et al 2000). 2: Additional trans-splicing in T. cruzi occur more frequently in rp genes.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether cis-splicing was also affected upon silencing the two proteins, we performed RT-PCR to detect the effects on the level of the PAP transcript, which undergoes both cis-and trans-splicing (26). The results, presented in Fig.…”
Section: Fig 4 the Level Of Sl Rna And The Y-structure Intermediatementioning
confidence: 99%
“…Trans-splicing evolved to separate long polycistronic transcripts. In trypanosomes, all mRNAs undergo trans-splicing, but cis-splicing also exists (26). All spliceosomal U snRNAs were identified in this organism (24).…”
mentioning
confidence: 94%